Peranan Posbakumadin dalam Kasus Pencurian dengan Pemberatan Pasal 363 Ayat 1 di Pengadilan Negeri Palembang - Pardiansyah Romli (Hakim, 2024)
In this research, it can be concluded that in the world of work, responsibility, thoroughness, high patience is required for the work carried out and discipline in work regulations and time discipline is our responsibility so that the tasks given can be completed on time. Based on the results of the discussion in accordance with the title proposed by the author, the author can draw the conclusion that: 1. The writer can find out the performance at Posbakumadin Palembang. 2. Preparers can know how to foster good relationships between colleagues and professionals. 3. The author can apply the learning theory chosen from the campus before the academic process at the research site.